Gout After Total Knee Arthroplasty - Chernoff, Daniel J. (Arthroplast Today, 2020)
Crystalline arthropathies are well-known pathologies in a native knee; however, the literature is scarce with regards to crystalline arthropathies in a total knee arthroplasty (TKA). The presentation of crystalline arthropathy in a TKA can be similar to a periprosthetic joint infection (PJI), making it difficult to distinguish between the 2 diagnoses. We present 1 case highlighting the similarity between crystalline arthropathy and PJI. A 71-year-old man with a history of bilateral TKAs presented with bilateral painful knee effusions and was initially presumed to have PJIs; however, he was later diagnosed with gout and successfully treated medically. A complete review of the literature demonstrates that crystalline arthropathies after TKA are infrequently reported and can be difficult to decipher from PJIs, and there is a lack of standardized treatment.